(تسمیہء ’غیر’(یورپی اور مسلم زبانوں میں مسلمانوں اور اہل مغرب کے نام - ڈاکٹر محمد خالد مسعود; عمر فاروق (FIKR-O NAZAR فکر ونظر, 2010)
Names of things illustrate the multilevel process of classification, on the basis of which various sciences have emerged. While naming the other is an attempt to identify the other and place him on one’s cultural map to facilitate dealing with him it is a function of language that adheres to cultural aspect which keeps changing with the passage of time. Nonetheless it is always marked with prejudices however minute they may be. In this context it has taken Western European languages several centuries to call a Muslim a Muslim. It is quite peculiar that in these languages Muslims were called by different names, which were probably neutral in their origins but most came to reflect hostility and contempt. An analysis of these names offers a good example for studying the process of naming the ’other’. This paper looks at these different names and tries to seek possible explanations for this naming process. For comparative purposes, the paper also includes a discussion of how Muslims named the others. Based on this analysis a general outline of the naming process is developed. This paper relies essentially on an analysis of the usage found in English, French, Spanish, Arabic, Persian and Urdu dictionaries for names for others in each of these languages. The translator has added up some notes of his own wherever he felt necessary.